Forest management planning in the Terai: sharing experiences from Sabaiya, Parsa - Thapa, Y.B.; Shaha, P.L.; Ghimire, B.; Arjun, K.C.; Karmacharya, S. (Banko Janakari, 2007)
The Ministry of Forests and Soil Conservation is in the process of developing operational forest management mechanisms for the Terai regions of Nepal. The Sabaiya pilot scheme in Parsa is under implementation, which witnessed experiences in several issues in the process. The paper aims to share technical experiences with wider audiences. It highlights anomalies in scheme estimation and final enumeration in basic stand parameters such as basal area and volume. It presents possible reasons and provide analysis and insights for future management planning of Terai forests. The paper concludes with a need for more technical information generation, analysis and utilisation approaches in forest management in Nepal. Key words: Forest management, stand parameters, volume table, Sabaiya Banko Janakari Vol.16(1) 2006 pp32-34